Comparison between BZAU, SRMI and MRM Conjugate Gradient Methods in Minimization Problems - Nurul Akmal Mohamed (Tanjong Malim, 2019)
Comparison between BZAU, SRMI and MRM Conjugate Gradient Methods in Minimization Problems by Nurul Akmal Mohamed